2014
DOI: 10.1111/jth.12710
|View full text |Cite
|
Sign up to set email alerts
|

Activated platelets present high mobility group box 1 to neutrophils, inducing autophagy and promoting the extrusion of neutrophil extracellular traps

Abstract: Summary Background Increasing evidence implicates both platelets and neutrophils in the formation, stabilization, and growth of peripheral and coronary thrombi. Neutrophil extracellular traps (NETs) play a key role. The early events in the deregulated cross‐talk between platelets and neutrophils are poorly characterized. Objectives To identify at the molecular level the mechanism through which platelets induce the generation of NETs in sterile conditions. Patients/Methods The presence of NETs was determined in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
501
2
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 444 publications
(550 citation statements)
references
References 60 publications
18
501
2
12
Order By: Relevance
“…45 Apoptosis has been described in inflammatory myopathies, 46,47 at least in some cases as a result of the cytotoxic action of T lymphocytes. Finally, the generation of neutrophil extracellular traps (NETs), an event strictly associated with the activation of autophagy pathway in inflammatory leukocytes 48 and modulated by the recognition of apoptotic cells, 49 has been described in the muscle upon ischemia-reperfusion injury. 50 Further studies will evaluate the relevance of NET contribution to muscle remodeling during autoimmune diseases and in homeostatic conditions.…”
Section: Unique Immune Privileges Of the Skeletal Musclementioning
confidence: 99%
“…45 Apoptosis has been described in inflammatory myopathies, 46,47 at least in some cases as a result of the cytotoxic action of T lymphocytes. Finally, the generation of neutrophil extracellular traps (NETs), an event strictly associated with the activation of autophagy pathway in inflammatory leukocytes 48 and modulated by the recognition of apoptotic cells, 49 has been described in the muscle upon ischemia-reperfusion injury. 50 Further studies will evaluate the relevance of NET contribution to muscle remodeling during autoimmune diseases and in homeostatic conditions.…”
Section: Unique Immune Privileges Of the Skeletal Musclementioning
confidence: 99%
“…been thought that extracellular HMGB1 is a late mediator of sepsis (29); however, it is also upregulated by activated platelets in the early phase of sepsis (30). HMGB1 acts as an early and late mediator of septic lethality.…”
Section: Figure 3 Sequential Changes In Blood Sample Values At 6 Hmentioning
confidence: 99%
“…HMGB1 has two nuclear localization sequences (NLSs) located in box A (aa [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] and between box B and the C tail (aa 179-185). Truncated mutants of HMGB1 identified that HMGB1 box B protein preserves the cytokine activity of HMGB1 (21), whereas recombinant box A protein acts as an antagonist of HMGB1 (22).…”
Section: Redox Regulation Of Hmgb1 Proinflammatory Activitiesmentioning
confidence: 99%